Grassland invasibility varies with drought effects on soil functioning. (September 2016) - Schrama, Maarten; Bardgett, Richard D.
Summary: Although it is known that ecosystems are more susceptible to invasion when disturbed, our knowledge of the mechanisms involved remains limited. Recent studies indicate that disturbance‐induced changes in soil nutrient availability could influence community invasibility, but the importance of this mechanism in the real world is not known. We tested the hypotheses that (i) exotic plant species profit from drought effects on soil functioning more than do natives; and (ii) grassland invasibility depends on soil responses to drought disturbance, which are greater in soils that exhibit a larger nutrient pulse following drought. This was tested in a series of grassland sites of contrasting management intensity which we subjected to an extreme (40‐day) drought, after which seeds from four different plant families of native species and related exotics were added to soils originating from the drought and control treatments under greenhouse conditions. We also examined the performance of seeded native species in the field. We expected that intensively managed grasslands with bacterial‐dominated soils would exhibit a larger nutrient pulse following drought, and hence a greater window of opportunity for invasion, than in extensively managed grassland soils with fungal‐dominated microbial communities. Results from the greenhouse experiment indicated that exotic species grew better in soil that had experienced drought, and had higher survival and growth rates than natives in both grassland types. Field results showed that drought increased invasibility in intensively managed grasslands, but had little impact on survival and growth of seeded species on extensively managed grassland soils. Increased invasibility of intensively managed grassland soils was associated with a significant soil nitrogen pulse following rewetting, which was not detected in the extensively managed grasslands. Synthesis . Our results indicate that intensively managed grasslands are more prone to invasion following drought than are extensively managed grasslands and that this response is in part related to differences in microbial community composition which regulate nutrient availability in soil following disturbance events. Given that extreme climate events are predicted to increase, our findings suggest that invasion of exotic species will increase in ecosystems with soils that are less resilient to disturbance. Abstract : Our results indicate that intensively managed grasslands are more prone to invasion following drought than are extensively managed grasslands and that this response is in part related to differences in microbial community composition which regulate nutrient availability in soil following disturbance events. Given that extreme climate events are predicted to increase, our findings suggest that invasion of exotic species will increase in ecosystems with soils that are less resilient to disturbance.